The Effect Of Interaction Between Hyper-Video Navigation Tools And The Cognitive Style In Raising The Level Of Learning Rate Of Students At The College Of Education (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this study is to determine the effect of the interaction between hyper-video navigation tools (buttons, cognitive maps, and hot spots) and cognitive style (independent of cognitive field / dependent according to the cognitive field) ا on the learning rate of the students at the Department of Education Technology. An experimental approach was used to compare six experimental groups (3*2). The research sample consisted of sixty sixth-grade students from the Department of Learning Techniques, College of Education, University of Jeddah. An embedded figure test (Embedded Figure Test) was used for e-learning technology to determine who is independent of the cognitive field and who is dependent according to the cognitive field. The research sample was divided into six experimental groups, each with ten students. An electronic achievement test was created to measure the learning rate of students. The results showed that the buttons were the appropriate navigation tool for both the independents and the dependents in the cognitive field. That is because the buttons take into account the individual differences between the students, it was concluded that it is the most appropriate tool for roaming through the hyper-video.